Archaeological research in the Lesser Slave Lake Region : a contribution to the pre-contact history of the boreal forest of Alberta - Le Blanc, Raymond Joseph (Mercury series., 2004)
"This new work presents the results of archaeological investigations carried out in the Lesser Slave Lake region of Alberta, Canada during the 1980s and 1990s. The book offers evidence of a long sequence of occupation in the area, beginning in late Holocene times. It also presents evidence of the extensive trade and communication networks which existed in the distant past, with raw materials arriving in the region from hundreds of kilometres away. The author also details cultural influences from areas to the north, as well as indications of contact with Plains groups to the south, and provides information relating to the Cree who lived in the area at the dawn of contact with Euro-Canadians."--BOOK JACKET.